Hippocampal but not amygdalar volume affects contextual fear conditioning in humans - Pohlack, Sebastian; Flor, Herta (Human brain mapping, 2012)
Both animal and human studies have identified a critical role of the hippocampus in contextual fear conditioning. In humans mainly functional magnetic resonance imaging has been used. To extend these findings to volumetric properties, 58 healthy participants underwent structural magnetic resonance imaging and participated in a differential fear conditioning paradigm with contextual stimuli. Ratings of emotional valence, arousal, and contingency as well as skin conductance responses (SCRs) were used as indicators of conditioning. Twenty‐nine participants with the smallest hippocampal volumes were compared with 29 persons with the largest hippocampal volumes. Persons with larger hippocampal volume (especially on the right side) learned to discriminate between two conditioned contexts, whereas those with small hippocampal volumes did not, as indicated by SCRs. Further analyses showed that these results could not be explained by amygdalar volumes. In contrast, the participant answers on the self‐report measures were not significantly influenced by hippocampal or amygdalar, but by total brain volume, suggesting a role of cortical structures in these more cognitive evaluation processes. Reanalysis of the self‐report data using partial hippocampal volumes revealed a significant influence of the posterior but not anterior subvolumes, which is in accordance with theories and empirical findings on hippocampal functioning. This study shows the relevance of hippocampal volume for contextual fear conditioning in healthy volunteers and may have important implications for anxiety disorders.
Gesehen am 06.04.2018